EFFECT OF RELIGIOSITY ON POLITICAL PARTICIPATION AND ATTITUDE TOWARDS GENDER ROLES - Bushra Javid; Rabeeta Zainab; Mussarat Jabeen Khan; Ayesha Sheikh; Iqra Altaf; Fiza Ejaz (International Journal of Contemporary Issues in Social Sciences, 2024)
Religiosity, Political Participation, and Attitude towards Gender Roles are one of the most essential constructs shaping a society and the three of them have been rarely studied together, especially in Pakistani population. So, a sample comprising of 400 adults across various cities strata was picked using non-probability sampling and was correlated. The surveys were comprised of three scales to measure the respective constructs. The results revealed that there exists a positive relation between Religiosity as a predictor and Political Participation as the outcome i.e., higher the religiosity, higher the political participation. Whereas, there is a negative relation between Religiosity as a predictor and Attitude towards Gender Roles as the outcome, implying that higher religiosity tends to create more negative or traditional attitudes towards gender roles. Moreover, Political Participation is also found to be significantly negatively correlated with Gender Role Attitudes. Age and gender are also found to be a significant determinant in predicting the three variables.